EFISIENSI DAN RISIKO PRODUKSI USAHATANI CABAI MERAH DI KABUPATEN BANTUL - , FAHMI ARDIANTO, Dr. Ir. Slamet Hartono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was held on the sandy and paddy field in Bantul District. The location which chosen purposively were Sanden and Kretek Sub-District. The aims of this research were to determine (1) factors that affecting red chili production in Bantul District (2) the level of allocative efficiency (price efficiency) of production factors in red chili farming (3) the level of production risk of red chili farming in Bantul District. The respondent waschosen by purposive random sampling, 16 farmers as a representative red chili farmers in each type of land. Log-linear regression function and Cobb-Douglas production function was used to analyze factors that affecting to the red chili production. allocative efficiency of production-factors used was determined by calculating the value of allocative efficiency index. Production risk of red chili was determined by calculating the variance coefficient. The factors affecting positively to the first planting season of red chili production were were land acreage, TSP fertilizer, KCL fertilizer, and land type. Factors that affecting to the second second planting season red chili production were land acreage, insecticide, fungicide, and land type. In the first planting season, the usage of land acreage, TSP fertilizer, and KCL fertilizer had been inefficient yet so its needed to be increased